Play between worlds : exploring online game culture - Taylor, T. L. (MIT Press, 2006)
"In Play Between Worlds, T.L. Taylor examines multiplayer gaming life as it is lived on the borders, in the gaps - as players slip in and out of complex social networks that cross online and offline space. Taylor questions the common assumption that playing computer games is an isolating and alienating activity indulged in by solitary teenage boys. Massively multiplayer online games (MMOGs), in which thousands of players participate in a virtual game world in real time, are in fact actively designed for sociability. Games like the popular EverQuest, she argues, are fundamentally social spaces."--Jacket